2005
DOI: 10.1158/1078-0432.ccr-04-2610
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Viral Therapy for Cervical and Ovarian Cancer Cells by Sindbis Virus AR339 Strain

Abstract: Purpose: Recently, the application of replication-competent viruses has been studied as anticancer agents. Sindbis virus (SIN) is an RNA virus that belongs to the Alphavirus genus in the Togaviridae virus family. The AR339 strain of SIN has not been reported to induce any serious disease to humans. Experimental Design: In this study, we evaluated the feasibility of the replication-competent SIN AR339 strain as an agent for cervical and ovarian cancer therapy. Results: SIN infection was able to induce cytopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…4,5 The range of viruses showing promise as oncolytic therapies for ovarian cancer is quite broad and includes reovirus, Newcastle Disease virus, echovirus Type I, Sindbis virus, mumps virus and engineered adenoviruses. [6][7][8][9][10][11][12][13] We previously reported that a genetically modified measles virus expressing a soluble marker peptide (MV-CEA) is a potent and selective oncolytic agent, with promising activity in preclinical models of ovarian cancer. 14 MV-CEA targets and causes extensive fusion in ovarian cancer cells through the CD46 receptor, which is expressed at high levels by many tumor types, including ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The range of viruses showing promise as oncolytic therapies for ovarian cancer is quite broad and includes reovirus, Newcastle Disease virus, echovirus Type I, Sindbis virus, mumps virus and engineered adenoviruses. [6][7][8][9][10][11][12][13] We previously reported that a genetically modified measles virus expressing a soluble marker peptide (MV-CEA) is a potent and selective oncolytic agent, with promising activity in preclinical models of ovarian cancer. 14 MV-CEA targets and causes extensive fusion in ovarian cancer cells through the CD46 receptor, which is expressed at high levels by many tumor types, including ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a replication-defective SIN viral vector was developed as a gene therapy vector for transient and high-level expression of heterologous genes (Tseng et al, 2004). However, replication-competent wildtype SIN has an additional favourable feature for a modality of cancer therapy (Unno et al, 2005). Replication-competent oncolytic viruses, like SIN used in this study, would not follow a simple dose -response curve.…”
Section: Discussionmentioning
confidence: 99%
“…Sindbis virus (SIN) is an RNA virus belonging to the Alphavirus genus in the Togaviridae virus family; it is transmitted to birds and mammals by mosquito bites (Jan and Griffin, 1999) and subsequently spreads throughout the body through the bloodstream (Tseng et al, 2002;Unno et al, 2005). It has the potential to induce apoptosis of infected mammalian cells (Jan and Griffin, 1999;Moriishi et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] There are increasing demands for anticancer therapy. [7] In vitro cytotoxicity testing procedures reduce the use of laboratory animals, [8] and hence use of cultured tissues, and cells have increased. [9] The discovery and identification of new antitumor drug with low side effects on the immune system have become an essential goal in many studies of immunotherapy.…”
mentioning
confidence: 99%